INFLUENCE OF INTERNAL COMMUNICATION ON INNOVATION PERFORMANCE OF DTS IN KENYA. - Njine, Grace Wanjiru; Nzulwa, Dr. Joyce; Kamaara, Dr. Mary; Ombui, Dr. Kepha (International Journal of Communication and Public Relation, 2017)
Purpose: The purpose of the study was to examine the influence of internal communication on Innovation Performance of DTS in Kenya. Methodology: This study adopted a descriptive survey design. The sampling frame of this study was derived from the database of the SASRA. Multistage sampling was used to select the sample of the study. The population of the study was the 181 DTS's operating in Kenya while the target population was 18 DTS's. The respondents were individual management staff. A questionnaire was used to gather primary data. Secondary data was collected through review of published literature such as journals articles, published theses and textbooks. Information was sorted, coded and input into the statistical package for social sciences (SPSS) version 21.0 for production of graphs, tables, descriptive statistics and inferential statistics. Results: The study found out that internal communication and innovation performance were positively and significantly related (r=0.277, p=0.000), Unique Contribution to Theory, Practice and Policy: The study recommended for Deposit Taking Sacco's to clearly communicate and explain their well formulated goals to staff. The ability to communicate will help the managers coordinate and collaborate their organizations' activities and actions in more effective and efficient manner. Keywords: Internal communication, Innovation Performance, DTS.